Luxury in jewelry design (Al-Academy, 2023)
The current research dealt with the presence of ornaments and jewelry since ancient times، which express the social، religious or emotional status of the person who adorns them، in addition to being distinguished by a distinct aesthetic and luxury، that is، in a sense closely related to the social and economic status of people، and we note that jewelry is considered a symbol of luxury and luxury، and hence The need to study luxury appeared in the design of ornaments and jewelry because it refers to the adornment elements that are made of metals and precious stones، which actually indicate signs of status or position that distinguish social classes from each other. The problem was identified by the following question: Determine the effectiveness of luxury in the design of jewelry and jewelry? The research included two important topics. We will address them successively.Below are some results and conclusions:1. Luxury is of great importance in the field of distinguished and luxurious creativity of the industrial designer and industrial production institutions in the modern industrial world.2. The emergence of luxury led to the fulfillment of the requests of users with trends and class of the velvet class of the rich، political figures، aristocratic classes and the global bourgeoisie.